New parallel strategies for block updating the QR decomposition - Kontoghiorghes, Erricos John (My University, 1995)
Parallel strategies are proposed for updating the QR decomposition of an m × n matrix after adding k rows (k ≫ n). These strategies are based on Givens rotations and are found to complete the updating in fewer steps by comparison to a recently published algorithm. An efficient adaptation of the first parallel strategy to compute the QR decomposition of structured banded matrices is also discussed in detail. ©
Keywords: Banded matrices; Givens rotations; Parallel algorithms; QR decomposition